Efektivitas Ekstrak Daun Kemangi Untuk Menurunkan Kadar Gas NH3 dan H2S Ekskreta Puyuh (Coturnix coturnix japonica) - M. W. Prayoga; Salundik; M. Ulfah (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2021)
Quail (Coturnix coturnix japonica) is one of the poultry produced meat and eggs commodity. The problem quail raising is excreta produces NH3 and H2S gases are chemicals in a free form and can pollute the environment. This study examines the effect of basil leaf extract on the reduction of NH3 and H2S quail excreta. Fresh excreta given extract with concentration level 200 mg mL-1, 150 mg mL-1, 100 mg mL-1, 50 mg mL then incubate for 24 hours. The method of basil leaf extraction by maceration soaking simplisia on ethanol 96% with comparison ratio 1:10. Antibacterial activity extract test used disc diffusion method. The inoculum contains 106 mL-1 bacterial cells S.aureus and E.coli are spreads on the MHA media then incubated at 37 oC for 24 hour. The result of this study that the levels of NH3 and H2S decreased (P<0.05) after given additional extract. Basil extract can inhibit bacterial activity S.aureus and E.coli (P<0.05). This study indicates that the additional basil leaf extract with a maximum concentration 200 mL-1 optimal can reduce NH3 and H2S gas levels compared to controls were not given additional extract.